Trans-Esterification of Poultry Skin Fat to Produce Biodiesel - Hafiz Anees Rehman; Syed Farman Ali Shah; Aziza Aftab; Zeenat M. Ali (Pakistan Journal of Analytical & Environmental Chemistry, 2016)
Chicken skin and its fat are sources of solid waste that are usually not utilized and add solid pollution. This research work deals with the production of useful biodiesel from utilizing the waste chicken (fat and its skins). Waste chicken fat and its skins (sourced from local shops of Hyderabad, Sindh, Pakistan) were extracted and trans-estrification was made. The product of trans-estrification was fatty acid methyl esters (FAME) commonly known as biodiesel. Sodium Hydroxide (NaOH) was used as catalyst and glycerol was obtained as a by-product. The FAME produced was tested for six parameters namely calorific value, cloud point, pour point, flash point, density and viscosity when compared to ASTM E2515-11 standard values. The results of this experiment showed that the calorific value, cloud point, pour point, flash point, density and viscosity values of FAME produced from chicken skin and its fat were close to that of petroleum derived diesel